(3JcfhdhLjG GOGQI GdTQGA h GdJNRjf (B/s - (3GdZOjQ, MeO QGTOs ((3YeGf(B: s (3OGQ RgQGf(B, s, 2010)
(3eGgjI hXjaI GdTQGA h JfXje GOGQI GdeTJQjGJ , GdGLQGAGJ GdYGeI aj hXjaI GdTQGA h SjGSGJ GdTQGA , ENJjGQ eUOQ GdJhQjO GdefGSH , GdCUhd GdYdejI ddTQGA , TQGA GdJLgjRGJ GdQCSeGdjI , GdGSJdGe h GdaMU , JNWjW GdeTJQjGJ h GdehGRfGJ GdJbOjQjI , Jbjje COGA h XjaI GdTQGA , eGgjI EOGQI GdeNGRf , GdeNGRf h ZLQGAGJ GdJNRjf h SLdGJ GdeNGRf , GdefGhdI aj GdeNGRf , ehbY h JUeje GdeNRf , LQO GdeNGRf h GdQbGHI Ydi GdeNRhf , SjGSGJ h JNWjW GdeNRhf , GdfeGPL GdeSJNOeI aj Jbjje hXjaI GdJNRjf , CeKdI JWHjbjI Ydi HYV GdfhGMj GdcejI (B.s
(3eQGLY U(B.369s
Keywords: (3COGQI GdeHjYGJs; (3GdTQGAs; (3JcfhdhLjGs